Chemical constituents from the rhizomes of curcuma zeoaria (Christm.) rosc. and the stems of citrus medica Linn - Subaidah Pomkeua (Prince of Songkla University, 2011)
Thesis (M.sc., Chemical Studies)--Prince of Songkla University, 2010